Law reports of Kenya - Pickering, George Hunter
Vols. for 1924-1956 contain cases determined by the Supreme Court of Kenya Colony and Protectorate; vols. for 1924-1933 contain also cases determined by the Court of Appeal for Eastern Africa, and by the Judicial Committee of the Privy Council on appeal from that court.